A generalization of translation surfaces with constant curvature in the isotropic space - Aydin, Muhittin Evren (Springer Basel Ag, 2016)
In this paper we study the translation surfaces generated by a space curve and a planar curve in the isotropic 3-space I-3. We completely classify such surfaces in I-3 with constant curvature. Several examples are also given by figures.
Keywords: Translation surface; space curve; isotropic space; isotropic mean curvature; isotropic minimal; relative curvature